Entrepreneurship as a career choice: An analysis of entrepreneurial self-efficacy and intention of university students - Lope Pihie, Zaidatol Akmaliah (Eurojournals, 2009)
A study was conducted to determine university students’ perceptions on entrepreneurial self- efficacy and entrepreneurial intention. Data were collected via questionnaire. The study utilized a descriptive research design and 1,554 university students participated in it. Each set of research constructs has a reliability value range between .74 and .96. Findings indicate that the students had moderate score on all constructs related to entrepreneurial intention and entrepreneurial self-efficacy in the aspects of management, financial and marketing. Moreover, students with positive entrepreneurial aspiration scored higher in entrepreneurship intention and self-efficacy which is significantly different from those who do not have positive aspiration. The students also scored moderately on attitudes towards entrepreneurial career and perceived behavioral control. The findings also indicate that those who perceived entrepreneurship need to be learnt at university have significantly higher mean score on attitudes towards entrepreneurial career as well as perceived behavioral control. Based on the findings of this study, it is suggested that to improve university students’ entrepreneurial intention and self-efficacy, certain teaching strategies needed to be conducted and university policy makers should add more value to their graduates by incorporating the elements that enhance the development of entrepreneurial intention and self-efficacy in the aspects of management, financial and marketing competencies as a basis to choose entrepreneurship as a career choice.